Ecosystem services of characteristic biotope types in the Ore Mountains (Germany/Czech Republic). Issue 1 (1st January 2017) - Bastian, Olaf; Syrbe, Ralf-Uwe; Slavik, Jan; Moravec, Jiři; Louda, Jiři; Kochan, Birgit; Kochan, Nils; Stutzriemer, Sylke; Berens, Astrid
ABSTRACT: The present transboundary study of ecosystem services (ES) focusses on a section of the Eastern Ore Mountains, a rural low mountain range in Germany and the Czech Republic. Aims of the study were to quantify five biotope types typical for the region (raised bogs, mountain meadows, clearance cairns, near-natural mountain forests, and near-natural streams), to identify some of the specific (not just monetary) values of nature in both countries, and to test appropriate ways to communicate ES aspects to stakeholders and the lay public. The study had to cope with country-specific differences in terms of data availability, valuation methods, landscape pecularities, and relations between supply and demand aspects. The ES were assessed using both expert-based ('ecological') assessments and economic valuations (e.g. calculation of prices and costs, revealed preferences). Among the provisioning ES, particularly biomass/fodder from meadows, wild fruit, and timber were taken into consideration; among the regulating ES, carbon sequestration and water regulation; and of the cultural ES, landscape aesthetics and recreation. The values of (near-)natural ecosystems in terms of regulating and cultural ES exceed those of provisioning ES by far. The results were also prepared for environmental education using new media, such as scouting games and virtual nature trails supported by mobile devices (smartphones, tablets, or GPS devices).EDITED BY Peter Schuhmann